Exploring In-hospital Death from Myocardial Infarction in Eastern Europe: From the International Registry of Acute Coronary Syndromes in Transitional Countries (ISACS-TC); on the Behalf of the Working Group on Coronary Pathophysiology & Microcirculation of the European Society of Cardiology - Bugiardini, Raffaele; Manfrini, Olivia; Majstorovic Stakic, Marta; Cenko, Edina; Boytsov, Sergei; Merkely, Bela; Becker, David; Dilic, Mirza; Vasiljevic, Zorana; Koller, Akos; Badimon, Lina (Current Vascular Pharmacology, 2014)
Introduction: The aim of the current study was to investigate the outcomes of coronary reperfusion therapies and ST-segment elevation myocardial infarction (STEMI) in patients of Eastern countries with economies in transition. Federation, and Serbia. The overall population consisted of 23,486 consecutive patients admitted to hospitals from January 1st to December 31st 2009. Registry data and statistics from the Organization for Economic Cooperation and Development (OECD) countries for the same period were used for comparison (2009-2010). In-hospital mortality was between 4% and 5% in the Western countries. In comparison mortality data were significantly larger in Serbia (10.8%) and Bosnia and Herzegovina (11.2%), intermediate in Russian Federation (7.2%) and similar in Hungary (5.0%). The rates of primary percutaneous coronary intervention (primary PCI) were very low in Bosnia and Herzegovina (18.3%), low in Russian Federation (20.6%) and Serbia (22%), and high in Hungary (70%). Major risk factors for death appear to be lack of reperfusion therapy, longer time delay from symptoms onset to hospital presentation as well as the higher percentage of patients with clinical presentation in Killip class III/IV. Conclusion: In-hospital STEMI case-fatality rates ranges widely in the former Eastern Bloc countries. Beyond the quality of care provided in hospitals, differences in time delay from symptoms onset to hospital admission may strongly influence STEMI patients’ outcome.
Keywords: mortality rate